Принципи генерування електроенергії безвідхідним способом - Грінченко Д. (Видавництво Національного університету «Львівська політехніка», 2000)
In the given article the possibility of generation of the electric power by a method almost without scraps and stated approaches in a solution of the delivered problem is shown.